PENGEMBANGAN ARSITEKTUR ENTERPRISE PADA DEPARTEMEN FINANCE (STUDI KASUS: DEALER MOBIL PT.XYZ) - Ngurah Suryantara, I Gusti; Ginting, Jusia Amanda; Sulaiman, Dewi Candani (ISTEK WIDURI, 2022)
Along with advances in technological developments, the development of making applications in a enterpriseis also experiencing development. This is in line with the increasingly complex business developments today. For this reason, careful planning is needed to invest in IT / IS (Information Technology / Information Systems) in a enterprise. The failure of IT/IS investment in a enterprise is one of the factors due to not having an IT/IS investment roadmap in a enterprise in the form of Enterprise Architecture. To get maximum results from an IT/IS investment in a enterprise, it is necessary to develop Enterprise Architecture. Enterprise architecture is a blueprint for a enterprise in achieving the enterprise's vision and mission supported by the implementation of IT/IS. So the selection of an Enterprise Architecture development framework is very important, one of the frameworks that can be used in the development of Enterprise Architecture such as the Zachman Framework. The Zachman Framework uses a 6-row and 6-column matrix to generate a blueprint. With the existence of the Enterprise Architecture blueprint, the enterprise can then use it for a roadmap for the development of applications needed by the enterprise, so that IT/IS technology investment in the enterprise can help the enterprise's business processes to achieve the vision and mission.